Peran Ekstrakurikuler Karawitan dalam Penguatan Karakter Cinta Tanah Air pada Era Revolusi Industri 4.0 di SD Negeri 2 Kedungmenjangan - Putri Wulandari; Pratik Hari Yuwono; Dedy Irawan (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to describe the role of musical extracurricular activities in strengthening the character of patriotism in the era of the industrial revolution 4.0 at SD Negeri 2 Kedungmenjangan. This research uses descriptive qualitative method. The subjects of this study include the principal, trainers, students and teachers. Data collection techniques using interviews, observation, and documentation. Data validity test uses source triangulation and technique triangulation. Data analysis techniques using the Miles & Huberman model which includes data collection, data reduction, data presentation and conclusion drawing. The results showed that: (1) extracurricular activities are held once a week on Saturdays after class hours, gamelan instruments are still complete, using the Surakarta style and Banyumasan style, Students are interested in joining extracurricular musical activities because of their own volition and support from parents. (2) The implementation of musical extracurricular can strengthen the character of patriotism by preserving arts and culture and being proud of the nation's work, Karawitan extracurricular activities also provide values ​​to students including the value of politeness, the value of mutual cooperation and the value of responsibility. (3) Supporting factors for musical extracurricular activities are the school environment, family environment and students' self, the inhibiting factor for musical extracurricular activities is the schedule of clashes with other activities and the development of technology.